From Play to Proficiency: The Power of the Word Connection Game on Students’ Vocabulary Development - Jihan Selasih S; Jamiluddin Jamiluddin; Afrillia Anggreni; Mochtar Marhum (MASI Mandiri Edukasi, 2025)
Currently, digital games dominate 21st-century classrooms; however, non-digital games remain valuable for promoting language learning, especially in areas with limited internet access. This study aimed to determine whether the Word Connection Game can enhance students’ vocabulary mastery. A quasi-experimental design was employed, involving two randomly selected classes: X M4 as the experimental group (28 students) and X M1 as the control group (28 students). Both groups were administered pre-tests and post-tests to collect data. The findings showed that the experimental group achieved a higher average post-test score (87.61) compared to the control group (60.68). The Mann–Whitney U test indicated a statistically significant difference between the groups (Asymp. Sig. 2-tailed = 0.000 < 0.05), supporting the alternative hypothesis. These results demonstrate that the Word Connection Game is an effective and engaging non-digital approach for enhancing students’ vocabulary skills. The study highlights that traditional game-based strategies remain valuable for fostering active learning and vocabulary retention, even in the digital era.